Invisible Lives: Gender, Dispossession, and Precarity amongst Syrian Refugee Women in the Middle East - Canefe, Nergis (Refuge: Canada’s Journal on Refugees, 2018)
This article attends to the connections between neo-liberal and neo-developmentalist labour regimes, asylum and immigration management, and the exploitation of undocumented, refugee, and migrant women, based on the experiences of Syrian refugee women in Turkey. The concept of precarity is explored as a selectively applied strategy by states to people who lack “status” or who are unable to benefit from “membership rights.” Forced migrants, illegal migrants, and asylum seekers are directly implicated in highly precarious work experiences at the bottom end of labour markets across the Global South, becoming trapped in forced labour and human trafficking arrangements. The article establishes a link between extreme forms of migrant labour exploitation in precarious life worlds and gender-based profiling of life chances.